Biological Characteristics, Impacts, and Management of Crenate Broomrape (Orobanche crenata) in Faba Bean (Vicia faba): A Review - Negewo, Takele; Ahmed, Seid; Tessema, Taye; Tana, Tamado (Frontiers in Agronomy, 2022)
Crenate broomrape, Orobanche crenata Forskal belong to family Orobanchaceae. It is a root holo-parasitic weed that devoid of chlorophyll and entirely dependent on host plants for its growth requirement. The parasite considerably infects plant species of Leguminosae, Apiaceae and Asteraceae families in highly infested drier and warmer areas of the world. It is well known for its devastating effects on cool-season food legumes especially on faba bean (Vicia faba L.) and threatening livelihood of subsistence farmers. Infected crop yield losses reach up to 100% depending on level of infection by the parasitic weed. Long-term impact of the parasite is even more serious than its short-term effects since its numerous minute seeds easily spread using different mechanisms and persist in soil up to 20 years. Besides, its management is difficult as no single method proved effective, economical and complete in managing the weed. This review paper gives an overview information on biological characteristics and harmful effects of crenate broomrape, and summarizes scientifically proven management techniques for its effective management. Different approaches should be validated, demonstrated and scaled for wider uses to manage crenate broomrape sustainably and boost the host crop productivity. Therefore, besides narrowing the knowledge gaps on the weed biology more strengthened efforts in searching for host plant resistance and/or tolerance based integrated management approaches by considering socio-economic and ecological conditions of faba bean growers are found paramount importance.